2020
DOI: 10.15282/jmes.14.1.2020.23.0508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation study of mild steel response to lateral quasi-static compression

Abstract: Collision of structure of a vehicle is not limited to the axial direction but it can occur laterally. The purpose of this paper is to present a study of the energy absorption behavior of different length of the circular mild steel tube under lateral crushing. A ring/tube (length of 10 mm, 35 mm, and 60 mm), 60 mm diameter and 1.5 mm thickness is compressed quasi-statically. Maximum loading setup to Instron machine was 50 kN. The speed of compression is 5mm/min. Finite Element Analysis (FEA) it used to validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…They revealed that the lateral loads and deformation modes were affected by the width of the platen, tube length, tube diameter, side length and diameter to thickness ratio. The no-orthogonal system of square and rectangular metal tubes is also experimentally and theoretically investigated and considered the energy dissipated by moved and stationary plastic hinges of the tube [9][10][11] . The tubes with small diameters and thick walls were found to have high lateral specific energy dissipation 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the lateral loads and deformation modes were affected by the width of the platen, tube length, tube diameter, side length and diameter to thickness ratio. The no-orthogonal system of square and rectangular metal tubes is also experimentally and theoretically investigated and considered the energy dissipated by moved and stationary plastic hinges of the tube [9][10][11] . The tubes with small diameters and thick walls were found to have high lateral specific energy dissipation 12,13 .…”
Section: Introductionmentioning
confidence: 99%